Teacher Readiness for Online Teaching Using Mobile Technology - Rahmania Rahmania; Dyah Sunggingwati; Ida Wardani (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
The purpose of this study was to determine the mobile technology used for online learning and the level of readiness of English teachers and non-English teachers at SMA 11 Negeri Samarinda and SMA AL-Khairiyah Samarinda 2021/2022. The research design is a survey design with a quantitative approach. The sample of this research is 113 teachers, classified as 107 non-English teachers and 6 English teachers. The questionnaire was adapted from Alwidi & Aldhaferi (2017). Based on the findings of this study, regarding teachers’ perception on their readiness in using mobile technologies and applications in class, the statement of four topics answered by the participants received a response that agreed (high), which this shows that they perceived that mobile learning is very helpful and supports this learning activity, as the teachers who were participants in this study stated that they knew and understood well how to use mobile learning. The results of the data on the level of readiness of Participant's pedagogical and technical classification between non-English teachers and English teachers the data analysis the participant's non-English teachers and English teachers show that teachers had prepared themselves with good pedagogical and technical readiness and, in the learning process, from the results of (Non English Teachers M = 3.54 and English teachers M = 3.66) which show that these teachers have good pedagogical and technical readiness